Attitudes of Local Population about Revitalization of Hunting Tourism in Tito’s Favourite Hunting Area “Karadjordjevo” - Besermenji, Snežana; Ristanovic, Branko; Ristic, Zoran; Manojlovic, Radoslava; Matejevic, Milosava (Turizam, 2025)
Convenient geographical position, variety of game, hunting tradition and hospitality culture contributed to the development of mass hunting tourism in Serbia in the end of the 20th century. Hunting activities were considerably developed on the territory of hunting area“ Karadjordjevo“, but the development stopped due to economical and political instability at the beginning of the 21st century. The aim of this research is to evaluate support of local population in the previously well-known hunting destinations nowadays when hunting tourism are under the pressure of different groups who underestimate their importance. Survey was conducted in the municipality of Backa Palanka in 2018, and the results show that the local population is generally prone to the revitalization of hunting tourism.
Keywords: hunting tourism; hunting; revitalization; Karadjordjevo; local community